2010
DOI: 10.1177/1077558710362538
|View full text |Cite
|
Sign up to set email alerts
|

Review: Quality of Mental Health Care for Nursing Home Residents: A Literature Review

Abstract: Because of the high proportion of nursing home residents with a mental illness other than dementia, the quality of mental health care in nursing homes is a major clinical and policy issue. The authors apply Donabedian's framework for assessing quality of care based on the triad of structure, process, and outcome-based measures in reviewing the literature on the quality of mental health care in nursing homes. Quality measures used within the literature include mental health consultations and hospitalizations, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 98 publications
0
95
1
Order By: Relevance
“…Most nursing homes do not have access to mental health providers. In a recent review of the literature on the quality of mental health care in nursing homes, Grabowski and colleagues (12) found that the treatment of mental health problems in nursing homes is often substandard. The American Geriatrics Society and the American Association for Geriatric Psychiatry (13) recommend setting policies that require nursing facilities to establish formal agreements with consulting mental health providers for ongoing training, consultation, and treatment services.…”
Section: Discussionmentioning
confidence: 99%
“…Most nursing homes do not have access to mental health providers. In a recent review of the literature on the quality of mental health care in nursing homes, Grabowski and colleagues (12) found that the treatment of mental health problems in nursing homes is often substandard. The American Geriatrics Society and the American Association for Geriatric Psychiatry (13) recommend setting policies that require nursing facilities to establish formal agreements with consulting mental health providers for ongoing training, consultation, and treatment services.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research documents concerns with mental health services provided in the NH (Grabowski, Aschbrenner, Rome, & Bartels, 2010) and concerns that NHs are being used as substitutes for inpatient psychiatric care (Simon, Lipson, & Stone, 2011). However, little is known about discharging this population specifically.…”
Section: Successful Strategies For Discharging Medicaid Nursing Home mentioning
confidence: 99%
“…Living in such institutions can result in social isolation, with the elderly person feeling deprived of his or her previous activities, thus decreasing their independence and functionality. Currently, most elderly persons living in Nursing Homes are affected by a disabling disease, dementia or terminal illness [1].…”
Section: Introductionmentioning
confidence: 99%